Ergodicity of polygonal slap maps - Del Magno, Gianluigi (2014)
We study the gap probabilities of the single-time tacnode process. Through steepest descent analysis of a suitable Riemann–Hilbert problem, we show that under appropriate scaling regimes the gap probability of the tacnode process degenerates into a product of two independent gap probabilities of the Airy processes.